Dynamic Modelling of a CPG-Controlled Amphibious Biomimetic Swimming Robot. (17th April 2013) - Ding, Rui; Yu, Junzhi; Yang, Qinghai; Tan, Min
This paper focuses on the modelling and control problems of a self-propelled, multimodal amphibious robot. Inspired by the undulatory body motions of fish and dolphins, the amphibious robot propels itself underwater by oscillations of several modular fish-like propelling units coupled with a pair of pectoral fins capable of non-continuous 360 degree rotation. In order to mimic fish-like undulating propulsion, a control architecture based on Central Pattern Generator (CPG) is applied to the amphibious robot for robust swimming gaits, including forward and backward swimming and turning, etc. With the simplification of the robot as a multi-link serial mechanism, a Lagrangian function is employed to establish the hydrodynamic model for steady swimming. The CPG motion control law is then imported into the Lagrangian-based dynamic model, where an associated system of kinematics and dynamics is formed to solve real-time movements and, further, to guide the exploration of the CPG parameters and steady locomotion gaits. Finally, comparative results between the simulations and experiments are provided to show the effectiveness of the built control models.